Novel Bioactive Compounds From Marine Sources as a Tool for Functional Food Development - Ghosh, Susmita; Sarkar, Tanmay; Pati, Siddhartha; Kari, Zulhisyam Abdul; Edinur, Hisham Atan; Chakraborty, Runu (Frontiers in Marine Science, 2022)
The marine environment is a relatively unexplored source of functional ingredients that can be used in food processing, storage, and fortification in a variety of ways. Marine microorganisms are a possible source of novel bioactive chemicals with potential human utility. Some of these microbes can live in the harsh marine environments, resulting in complex compounds with unique biological properties that can be used in several industrial and biotechnological applications. So far, several marine microorganisms (fungi, myxomycetes, bacteria, and microalgae) have been isolated that produce antioxidant, antibacterial, apoptotic, antitumoral, and antiviral chemicals. Furthermore, it emphasizes the enormous potential for marine microbes to produce very important bioactive chemicals. The main goal of this review is to provide a concise overview of several constituents of marine bioactives. Anticoagulant, anticancer, and hypocholesterolemic effects have been demonstrated for bioactive peptides extracted from fish protein hydrolysates, as well as algal fucans, galactans, and alginates. Furthermore, omega-3 fatty acids are abundant in fish oils and marine microorganisms, while potent antioxidants such as carotenoids and phenolic compounds can be found in crustaceans and seaweeds. This review focuses on the potential use of marine-derived chemicals as functional food ingredients for health maintenance and chronic disease prevention, based on their bioactive qualities.